2022
DOI: 10.1364/oe.456559
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental performance evaluation of a laser-concentrated photovoltaic-thermoelectric generator hybrid system

Abstract: Thermal management of concentrated photovoltaic (CPV) modules is essential to avoid the decrease in conversion efficiency caused by temperature rise during their operation. This is even more important for laser-concentrated CPV hybrid systems where out-of-control temperature rise is more likely to happen. In this research, a three-dimensional simulation model for a concentrated photovoltaic-thermoelectric (CPV-TE) hybrid system was studied to optimize its parameters and improve its conversion efficiency under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…Similarly, we assumed a convection heat transfer coefficient of 9.5 W/(m 2 K) which corresponds to the wind speed of 1 m/s (using Equation ( 12)). This value may be different from what Li et al [18] considered because it was not explicitly stated. Since the PV is sensitive to both the thermal resistance and the convection coefficient, its output values may differ if any of the parameters is different from that of the reference.…”
Section: Cpv-te Model Validationcontrasting
confidence: 57%
See 4 more Smart Citations
“…Similarly, we assumed a convection heat transfer coefficient of 9.5 W/(m 2 K) which corresponds to the wind speed of 1 m/s (using Equation ( 12)). This value may be different from what Li et al [18] considered because it was not explicitly stated. Since the PV is sensitive to both the thermal resistance and the convection coefficient, its output values may differ if any of the parameters is different from that of the reference.…”
Section: Cpv-te Model Validationcontrasting
confidence: 57%
“…Similarly, as the incident power increases, the temperature gradient across the TEM increases, and this led to an increase in the output power of the TEM. Furthermore, some assumptions made by Li et al [18] (blue line) were not reported in the paper. For example, the thermal resistances between the PV and TEG, TEG, and heat sink were not reported.…”
Section: Cpv-te Model Validationmentioning
confidence: 87%
See 3 more Smart Citations